Gestão baseada em competências por órgãos e entidades públicas do Rio de Janeiro - Souza, Camila Rodrigues de (2010)
The objective of the present dissertation is to identify if management based on competences is viable in organs and entities of the public administration in the state of Rio de Janeiro and why. For the study, bibliographical and field researches were accomplished in Tribunal de Justiça do Rio de Janeiro, Furnas and Banco do Brasil. The data were treated through the method Map of Association of Ideas. The results point that the management based on competences is considered a vector of structural and cultural changes and a tool that generates clear and real information for the management of people in the searched institutions. Also they disclose some problems, as the rigid and constant fiscalization of external agencies and the influence of aspects politicians in the management of institutions of the public administration. Although the barriers found for its implementation, the study concludes that the management based on competences is viable in public organs and entities and can be considered a way of transformation and modernization of the management of people in the Brazilian public service.